Antibacterial Activity of the Epidermal Mucus of Barbodes everetti - Jiazhen, Lim; Yang, Lee; Badiozaman, Sulaiman; Lesley Maurice, Bilung; Yee, Ling Chong (Universiti Malaysia Sarawak (UNIMAS), 2018)
The epidermal mucus of fish contains antimicrobial agents that act as biological defence against disease. This study aims to identify antibacterial activity and protein concentration of epidermal mucus of Barbodes everetti, a Bornean endemic freshwater fish. The epidermal mucus was extracted with 3% acetic acid, 0.85% sodium chloride and crude solvents. The mucus activity against eight strains of human pathogenic bacteria, including Bacillus cereus ATCC 33019, Escherichia coli O157:H7, Listeria monocytogenes ATCC 7644, Pseudomonas aeruginosa ATCC 27853, Salmonella braenderup ATCC BAA 664, Salmonella typhimurium, Staphylococcus aureus ATCC 25933, and Vibrio cholerae, were tested. The acetic acid mucus extract of B. everetti was able to inhibit five strains of bacteria and show no activity toward E. coli O157:H7, B. cereus ATCC 33019 and L. monocytogenes ATCC 7644. Moreover, the highest protein concentration was quantified in crude extract, followed by aqueous and acetic acid extracts. This study provides a preliminary knowledge on the activity of epidermal mucus of B. everetti towards five out of the eight human pathogens tested, therefore it may contain potential sources of novel antibacterial components which could be further extracted for the production of natural antibiotics towards humanrelated pathogenic bacteria.